Potency of Yeast from Orange Peel’s Ecoenzyme as Antimicrobe - Elsa Sri Handayani; Dezi Handayani; Irdawati Irdawati; Violota Violita (Jurnal Serambi Biologi, 2023)
Orange peels can still be utilized even though they are categorized as waste. Orange peels still have quite a lot of nutrients and contain various active compounds. Orange peels can be used as a source of organic material for the manufacture of ecoenzyme. The ecoenzyme produced from orange peel has a distinctive and fragrant aroma so that it is preferred compared to ecoenzyme made from other organic materials. During the ecoenzyme fermentation process, there are various types of bacteria and fungi that grow, but their roles are not yet known. The results of previous research obtained eight yeast isolates from the fermentation process of orange peel ecoenzyme, but only six isolates can be tested because two isolates are contaminated. The purpose of this study was to see the potential of yeast from citrus peel ecoenzyme as an antimicrobial. The antimicrobial activity test method used was the agar solid diffusion test. The presence of antimicrobial activity is characterized by a zone of inhibition around the colony of yeast isolates. The results showed that all isolates of yeast from orange peels ecoenzyme were able to inhibit the growth of E. coli and only five isolates were able to inhibit the growth of S. aureus, but none were able to inhibit C. albicans. The diameter of the inhibition zone against E. coli ranged from 8.3 mm to 17.5 mm while S. aureus ranged from 7.8 mm to 12.9 mm. Therefore, yeast derived from orange peel ecoenzyme has potential as an antimicrobial, especially against E. coli. and S. aureus.